The Effect of Leadership Style, Non-Physical Work Environment, and Compensation on Employee Performance at CV Sujinah Grobogan Regency - Exis Zaimul Haq Attaqy; Wijiastuti, sri; Widodo, Zandra (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyse the influence of leadership style, non-physical work environment, and compensation on employee performance at CV Sujinah, a company engaged in plant seedlings. The method used in this research is primary data collection through questionnaires distributed to 82 employees. Data analysis was conducted using Statistical Package for the Social Sciences (SPSS) to test the hypothesis and measure the effect of independent variables on the dependent variable. The results showed that leadership style, non-physical work environment, and compensation have a positive and significant influence on employee performance. The results showed that partially leadership style affects employee performance by 14.4%. The non-physical work environment has an effect of 31.5%, and compensation has an effect of 35.2%. While the results of the coefficient of determination show that (adjusted R Square) is 0.429. This means that the variation in employee performance variables (Y) can be explained by the variation in the independent variables X1 (leadership style), X2 (non-physical work environment) and X3 (compensation) by 42.9%. The rest (100%-42.9% = 57.1%) is explained by other variables.